ARCHETYPE OF PATRIARCHY IN SAHAR KHALIFEH’S WILD THORNS - Saqer Salameh Ahmad Sahmasin Khresheh; Dr. Ady Radwan (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Wild Thorns by Sahar Khalifeh emphases on the Zionist occupation of Palestine. It reflects the Zionist occupation as patriarchy. This research aims at inspecting the type of occupation that has been symbolized in the form of patriarchy in Wild Thorns. The research has been directed depending on Jungian criticism that interprets literature as a source of “archetypes”. Therefore, the research aims at interpreting the archetype of patriarchy proposed in Freud’s Totem and Taboo. Depending on this theory, humanity experienced father dominance over children and wives. Accordingly, a revolution or resistance by children and wives is justified due to the bad deeds imposed by the father dominance. In such a way, Patriarchy is embodied in Wild Thorns by the depiction of the relationship between the occupier and the occupied that enables Israel to play the role of a father who imposed bad regulations that made people live in Palestine difficult.